2012
DOI: 10.1556/avet.2012.016
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the antibiotic resistance and biofilm formation of Staphylococcus aureus strains isolated from gangrenous mastitis of ewes

Abstract: In this study, Staphylococcus aureus strains (n = 110) isolated from seven ewe flocks in Sanliurfa, Turkey were screened for antibiotic resistance and biofilmforming ability as well as for genes associated with antibiotic resistance and biofilm-forming ability. All isolates were found to be susceptible to oxacillin, gentamicin, clindamycin, cefoxitin, tetracycline, vancomycin, amoxicillin-clavulanic acid, ciprofloxacin and sulphamethoxazole-trimethoprim. The percent proportions of strains resistant to penicill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 19 publications
2
11
1
Order By: Relevance
“…, 2001 ). The present results differ from those reported by Tel et al (2012) who analyzed 110 S. aureus strains isolated from cases of sheep clinical mastitis. The isolates did not carry the bap gene, but were positive for the icaA and icaD genes.…”
Section: Discussioncontrasting
confidence: 99%
“…, 2001 ). The present results differ from those reported by Tel et al (2012) who analyzed 110 S. aureus strains isolated from cases of sheep clinical mastitis. The isolates did not carry the bap gene, but were positive for the icaA and icaD genes.…”
Section: Discussioncontrasting
confidence: 99%
“…The presented data of the DNA microarray analysis revealed that all S. aureus isolates harbored icaACD genes regardless of their origin. These results were in agreement with several findings made in human infections [46], human nasal samples [47], sheep mastitis [48], and isolates from food matrices [6].…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have been conducted worldwide on toxic genes of MRSA from various dimensions. In similar clinical studies, the frequency of sea gene of MRSA was 58.8% in Gorgan-Iran, 74.4% in Tehran-Iran, 33% in China, and 12% in Germany, while the frequency of sea gene in MRSA isolates from various specimens obtained in this study was 25% which is similar to that of the study conducted in Korea [ 10 , 23 - 26 ]. Moreover, the frequency of sub gene has been investigated in many studies.…”
Section: Discussionsupporting
confidence: 87%